Urbanization and Urban Growth Dynamics: A Study on Chittagong City - Samad, Rokshana Binta; Chisty, Kutub Uddin; Rahman, Ataur (Journal of Bangladesh Institute of Planners, 2015)
The process of urbanization is a universal phenomenon. All countries are prone to this because of increasing population and economic development. Urban growth refers to an increase in total urban population. The size of urban population growth in the next four decades, especially in developing countries will be massive. Thus rapid urban growth introduces new urbanization challenges when resource is limited. Urbanization has been globally recognized as an effective engine of economic growth and socio-cultural development. Rapid urban growth has created huge demands on urban utilities and services as well. The negative consequence of rapid urbanization has occurred massive scale urban environmental degradation. For this research Chittagong city corporation area has been selected as a study area. Pairwise ranking is used to rank a list of urban growth factors in priority order. Holden method has been used in this research for identifying the percentage of population growth and Percentage of unorganized urban growth which is related to urban sprawl. Urban growth pattern has been identified by some growth indicator methods such as Moran Coefficient, Shannon’s entropy, and Geary’s coefficient. All spatial and temporal data is collected from secondary source. GIS and Remote Sensing approach has been used for data exploration to indicate urban growth pattern and land use change. Understanding the urban growth pattern would help in addressing the present and future needs of a city. This will further help in preparation of effective planning and management strategies for controlled and systematic urban growth both at regional as well as local level. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 167-174